2016
DOI: 10.1002/2015ja021990
|View full text |Cite
|
Sign up to set email alerts
|

O+ and H+ above the polar cap: Observations and semikinetic simulations

Abstract: A one‐dimensional direct simulation Monte Carlo model is used to study the outflow of O+ and H+ ions from 1.2 RE to 15.2 RE along two flight trajectories originating from the polar cap, namely, the central polar cap (CPC) and the cusp. To study the effect of varying geophysical conditions and to deduce the proper set of parameters, several parameters were varied, and the results were compared to corresponding data from Cluster spacecraft. First, several sets of diffusion coefficients were considered based on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Finally, from the interpolated electric field, a new velocity is calculated with the Boris algorithm (e.g. Birdsall and Langdon, 1991). The last step is repeated as far as the limitations of the code allow it.…”
Section: Particle Tracing Simulationsmentioning
confidence: 99%
“…Finally, from the interpolated electric field, a new velocity is calculated with the Boris algorithm (e.g. Birdsall and Langdon, 1991). The last step is repeated as far as the limitations of the code allow it.…”
Section: Particle Tracing Simulationsmentioning
confidence: 99%
“…At an altitude range of 1.2 Re to 15.2 Re, Barghouthi et al (2016) employed the same 1-D Monte Carlo model used by Abudayyeh et al (2015) to investigate energetic H + and O + outflows along two trajectories (from the polar cap to the cusp) and compared them with Cluster data. Considering the centrifugal acceleration, the ambipolar electric field and the waveparticle interaction, they concluded that the latter was the most important mechanism especially at higher altitudes (cusp).…”
Section: Introductionmentioning
confidence: 99%